2019
DOI: 10.1177/0956462419855828
|View full text |Cite
|
Sign up to set email alerts
|

Intra-anal use of imiquimod: what is the clinical evidence?

Abstract: Imiquimod has been demonstrated to be rather effective in patients with anal as well as perianal high-grade squamous intraepithelial lesions (HSILs). Nevertheless, until now the intra-anal use of imiquimod has been considered off-label. The aim of this study is to review the clinical evidence related to the intra-anal use of imiquimod in the treatment of human papillomavirus-related anal lesions. A systematic search in PubMed and Scopus was performed. In total, 422 patients were included. The most common refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Imiquimod acts as an agonist of Toll-like receptor-7. It Research, Society and Development, v. 11, n. 2, e31511225710, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org /10.33448/rsd-v11i2.25710 activates nuclear factor kappa-B, stimulating the dermal dendritic cells to express cytokines, such as tumor necrosis factor-a, interferon-a (IFN-a), and interleukins 1, 6, 8, and 12 at the site of application (Gkegkes et al, 2019). Consequently, imiquimod stimulates the immune system to release several cytokines, which are essential in the elimination of viruses and destruction of neoplastic cells (Knottenbelt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imiquimod acts as an agonist of Toll-like receptor-7. It Research, Society and Development, v. 11, n. 2, e31511225710, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org /10.33448/rsd-v11i2.25710 activates nuclear factor kappa-B, stimulating the dermal dendritic cells to express cytokines, such as tumor necrosis factor-a, interferon-a (IFN-a), and interleukins 1, 6, 8, and 12 at the site of application (Gkegkes et al, 2019). Consequently, imiquimod stimulates the immune system to release several cytokines, which are essential in the elimination of viruses and destruction of neoplastic cells (Knottenbelt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-specific T-cells are multiplied and infiltrate the affected area. At the same time, B cells start producing antibodies that subsequently increase antigen presentation (Gkegkes et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent small, single center, longitudinal cohort study of MSM living with HIV and diagnosed with HSIL found excellent response rates and tolerability of imiquimod with less recurrence compared to surgical treatment [4]. In a systematic review of 14 studies of intraanal imiquimod, complete response in 211 patients with HSIL was observed in 35%, partial response 20.9% and recurrence in 15% [16]. Differences in the response rates may be related to patient factors such as extent of disease, degree of immunosuppression or other risk factors such as smoking but also to the dose of imiquimod or the formulation (cream vs suppository versus tampon) [16].…”
Section: Plos Onementioning
confidence: 99%
“…Cuando se utiliza en mucosas puede desencadenar un síndrome similar al gripal. 93 Los efectos adversos locales están íntimamente asociados al modo de acción y pueden ser manejados adecuando la frecuencia de aplicación.…”
Section: Tratamientounclassified
“…Las tasas de recurrencia fueron 15% para HSIL y 20% para condilomas. 93 En un ensayo controlado y aleatorizado, 64 pacientes HSH con HIV con HSIL endoanal recibieron imiquimod al 5% o placebo, ambos aplicados en el conducto anal tres veces por semana durante cuatro meses. De 28 pacientes que completaron el tratamiento, cuatro tuvieron resolución completa y ocho disminuyeron su grado a LSIL.…”
Section: Tratamientounclassified